Landlessness and farm invasions in Zimbabwe: lessons for social workers practicing community work - Kaseke, Edwin; Gumbo, Perpetual (2001)
The invasion of white-owned farms in Zimbabwe by groups of war veterans and other landless peasants has attracted worldwide attention. This article starts by discussing the farm invasions which have occurred in the country as a consequence of the landlessness problem. The authors argue that the delay in solving the land crisis has forced the war veterans to invade the farms as social action against both the central government and the white commercial farmers who are the predominant owners of the land. Three different strategies in community work are conceptualized before the lessons that social workers practicing community work can draw from the farm invasions as a social action strategy are discussed. - Reproduced
Keywords: Social workers - Zimbabwe; Land reform - Zimbabwe; Land tenure - Zimbabwe; Land tenure